Childhood family factors predict developmental trajectories of hostility and anger: a prospective study from childhood into middle adulthood. Issue 11 (November 2013) - Hakulinen, C.; Jokela, M.; Hintsanen, M.; Pulkki-Råback, L.; Hintsa, T.; Merjonen, P.; Josefsson, K.; Kähönen, M.; Raitakari, O. T.; Keltikangas-Järvinen, L.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Low socio-economic status (SES), and a conflictive, cold and unsupportive family environment in childhood have been associated with early adulthood hostility. However, it is unknown whether this association changes in magnitude with age from childhood to adulthood. We investigated whether childhood family factors (SES and parental child-rearing style) predicted differential development of offspring hostility and anger from early to middle adulthood. Method Between 2041 and 2316 participants (age range 3–18 years at baseline) were selected from the longitudinal Young Finns study. The participants were followed for 27 years between 1980 and 2007. Childhood SES and parent's self-reported child-rearing style were measured twice: at baseline and 3 years after baseline. Hostility and anger were assessed with self-report questionnaires at 12, 17, 21 and 27 years after baseline. Results Low parental SES and hostile child-rearing style at baseline predicted higher mean levels of offspring anger and hostility. Low parental SES and one of the hostile child-rearing style components (strict disciplinary style) became more strongly associated with offspring hostility with age, suggesting an accumulating effect. Conclusions Childhood family factors predict the development of hostility and anger over 27 years and some of these family factors have a long-term accumulating effect on the development of hostility.